Who I Am and How I Contract: The Effect of Contractors’ Roles on the Evolution of Contract Structure in University–Industry Research Agreements - Bercovitz, Janet E. L.; Tyler, Beverly B. (Organization Science, 2014)
In this exploratory study of university–industry sponsored research agreements, we investigate how organizational roles direct the relational learning of contracting personnel, which subsequently influences contract evolution. Integrating theory with comments from field interviews, we posit that as scientists gain contracting experience with an exchange partner their focus of attention on knowledge creation supports the establishment of a relationship based on technical competence, behavioral experience, and operational routines that cause the enforcement terms of subsequent contracts to become less detailed. We also submit that contract administrators, because of their focus on knowledge protection (mitigating opportunism and enforcement), primarily accumulate joint governance experience and establish administrative routines that cause the enforcement terms of subsequent contracts to become more detailed. Rich content analysis of monitoring and intellectual property terms of sponsored research agreements supports our theoretically grounded hypotheses.